Fuel cell systems reliability and availability enhancement by developing a fast and efficient power switch open-circuit fault detection algorithm in interleaved DC/DC boost converter topologies. (14th September 2016) - Guilbert, Damien; N'Diaye, Abdoul; Gaillard, Arnaud; Djerdir, Abdesslem
Abstract: Due to the low and unregulated voltage generated by fuel cells, power electronic conditioning systems such as DC/DC converter are required in Fuel Cell Systems (FCS). These FCS are used in different applications with critical loads such as automotive applications, material handling equipment, and backup power. In these applications, it is crucial to guarantee reliability and availability. In FCS, DC/DC converters are one of the most important failure sources. Since the power switches ranked the most delicate components in DC/DC converters, the development of power switch fault detection algorithm is a mandatory step in order to ensure the availability of the system. The purpose of this paper is to propose a fast and original power switch fault detection algorithm based on Park's vectors combined with a Fault-Tolerant Control (FTC) for a 3-leg Interleaved DC/DC Boost Converter (IBC) used in FCS. The developed power switch fault detection and FTC are implemented on a FPGA target, allowing detecting, identifying and handling quickly the faulty power switch. The obtained results from experimental tests confirm the excellent performances of the proposed power switch fault detection algorithm and the FTC. Highlights: A thorough review is given concerning fault-tolerance studies in fuel cell systems. Investigations of power switch failures tolerance in interleaved DC/DC converters. Development of a fault detection algorithm and fault-tolerant control. Implementation of a fault detection algorithm on a FPGA target. Performances of the fault detection algorithm to detect the faulty power switch.